Customer Satisfaction Towards Nostalgic Products - Subramaniam, Aswathy; Rathnapriya , Dr.B. (International Journal of Accounting and Economics Studies, 2025)
Nostalgia is a sentimental feeling of affection for the past, especially for a particular period or place with a lot of happy moments. This complex, multifaceted phenomenon has been influencing emotions, consumer behavior, and cultural trends. Understanding how nostalgia shapes individual and collective experiences could prove to be of immense value to marketers, policymakers, and researchers alike. Customer satisfaction with nostalgic products refers to the emotional and psychological response of customers towards products that evoke memories and feelings from the past. This study provides a comprehensive overview of customer satisfaction with nostalgic products, covering key drivers, benefits, factors influencing satisfaction, measurement tools, implications for businesses, challenges, and future research directions.The primary goal of this article is to explore what makes customers loyal to nostalgic products. This study examines consumer satisfaction with nostalgic products, factors influencing customer satisfaction, and the variables that affect people's decisions. It also considers the consequences for companies and focuses on direct feedback from 150 participants. The results indicate that the age group between 30-40 years is more satisfied with nostalgic products, and factors such as choice, brand loyalty, empathy, and language play a major role in influencing customer satisfaction. Furthermore, this study investigates how companies can leverage nostalgia to improve brand loyalty and establish a better connection with consumers through product creation, branding, and marketing tactics. By understanding the characteristics that influence consumer inclination towards nostalgic merchandise, companies can successfully customize their products to satisfy customer needs and harness the enduring appeal of nostalgia in the current market.Objectives of the Study: To find factors influencing customer satisfaction toward nostalgic products.Research Methodology• This study basically depends on original information gathered through inquiry• Primary data were collected through a structured questionnaire (Google Form)• Data were collected by convenience sampling method from 150 respondents.• The analysis was made through Simple percentage & Factor analysis MethodResult:Majority of customers who choose nostalgic product are 30-40yrs. The analysis of the data reveals important insights into customer satisfaction with nostalgic products. The Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy is 0.703, indicating that the sample size is sufficient for factor analysis. Bartlett's test of sphericity yields a significant result with a chi-square value of 249.934 and a p-value of 0.000, confirming that the correlations among variables are adequate for factor extraction.The rotated component matrix identifies three factors. The first factor, with high load on variables such as choice (0.764), brand loyalty (0.732), convenience (0.601), quality (0.509), and simplicity (0.501), represents product features and customer preferences. The second factor emphasizes customer service and communication, as indicated by high loading on empathy (0.717), language (0.668), and appreciation (0.612). The third factor reflects operational efficiency and pricing, with significant loadings on response time (0.673), reasonable price (0.574), and accessibility (0.461).These three factors collectively explain 47.434% of the variance in the data, with individual contributions of 22.106%, 15.475%, and 9.853%, respectively. This analysis highlights that product attributes, customer interactions, and operational aspects play key roles in shaping customer satisfaction with nostalgic products.Conclusion: This research reveals a positive correlation between nostalgic products and customer satisfaction, highlighting the profound influence of nostalgia on consumer experiences. The findings suggest that nostalgic products evoke positive emotions, increase brand loyalty, and drive purchasing decisions. Managers and marketers can leverage nostalgia by incorporating retro designs, re-releasing classic products, and emphasizing sentimental value. However, companies must balance nostalgia with innovation to avoid perceived stagnation. Future research can be conducted in the long-term effects of nostalgia on customer satisfaction and further strategies for maintaining nostalgic appeal.
Keywords: Nostalgic Products; Customer Satisfaction; Childhood Memories